Design of Robust Current Controller for Two-Level 12-Pulse VSC-based STATCOM. (16th June 2011) - Janaki, M.; Thirumalaivasan, R.; Prabhu, Nagesh
Abstract : The static synchronous compensator (STATCOM) is a shunt connected voltage source converter (VSC) based FACTS controller using GTOs employed for reactive power control. A typical application of a STATCOM is for voltage regulation at the midpoint of a long transmission line for the enhancement of power transfer capability and/or reactive power control at the load centre. The PI controller-based reactive current controller can cause oscillatory instability in inductive mode of operation of STATCOM and can be overcome by the nonlinear feedback controller. The transient response of the STATCOM depends on the controller parameters selected. This paper presents a systematic method for controller parameter optimization based on genetic algorithm (GA). The performance of the designed controller is evaluated by transient simulation. It is observed that the STATCOM with optimized controller parameters shows excellent transient response for the step change in the reactive current reference. While the eigenvalue analysis and controller design are based on D-Q model, the transient simulation is based on both D-Q and 3-phase models of STATCOM (which considers switching action of VSC).